The Relationship Between Interpersonal Violence Victimization and Smoking Behavior Across Time and by Gender. Issue 1 (2nd April 2016) - Kristman-Valente, Allison N.; Oesterle, Sabrina; Hill, Karl G.; Wells, Elizabeth A.; Epstein, Marina; Jones, Tiffany M.; Hawkins, J. David
Abstract : This study examined relationships between interpersonal violence victimization and smoking from childhood to adulthood. Data were from a community-based longitudinal study (N = 808) spanning ages 10 to 33. Cross-lag path analysis was used to model concurrent, directional, and reciprocal effects. Results indicate that childhood physical abuse predicted smoking and partner violence in young adulthood; partner violence and smoking were reciprocally related in the transition from young adulthood to adulthood. Gender differences in this relationship were not detected. Social work prevention efforts focused on interpersonal violence and interventions targeting smoking cessation could be critical factors for reducing both issues.